Structural, compositional, and biomechanical alterations of the lumbar spine in rats with mucopolysaccharidosis type VI (Maroteaux–Lamy syndrome). Issue 4 (28th November 2012) - Lai, Alon; Simonaro, Calogera M.; Schuchman, Edward H.; Ge, Yi; Laudier, Damien M.; Iatridis, James C.
Abstract Mucopolysaccharidosis (MPS) VI is an inherited lysosomal storage disorder resulting from deficiency of N‐acetylgalactosamine‐4‐sulfatase activity and subsequent accumulation of incompletely degraded dermatan sulfate (DS) containing glycosaminoglycans (GAGs). Painful spinal deformities are commonly found in MPS VI patients. We characterized lumbar spine structure, composition, and biomechanics in a naturally occurring rat MPS VI model and evaluated the role of MMP‐13, ADAMTS‐5 and TNF‐α in modulating the observed changes. MPS VI rats had discs with large vacuolated cells and sizable nuclear defects. MPS spine segments also had structural and functional changes suggestive of spinal instability, including decreased nuclear pressurization, increased joint laxity and increased disc height index. These functional changes were at least partly associated with elevated ADAMTS‐5, MMP‐13, and TNF‐α. Vertebral and endplate biomechanics were also affected by MPS VI with decreased failure load and stiffness. The discal and vertebral dysfunctions observed in MPS VI rats are likely to be associated with pathological spinal conditions, similar to those that afflict MPS patients. Our findings also suggest more broadly that abnormal accumulation of GAGs and the associated chronic pro‐inflammatory and catabolic cascade may also be a source of spinal dysfunction. © 2012 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 31: 621–631, 2013